Magnetoelectric coupling in iron oxide nanoparticle—barium titanate composites. (29th November 2018) - Wang, Li-Ming; Petracic, Oleg; Mattauch, Stefan; Koutsioumbas, Alexandros; Wei, Xian-Kui; Heggen, Marc; Leffler, Vanessa; Ehlert, Sascha; Brückel, Thomas
Abstract: Ferrimagnetic iron oxide nanoparticle monolayers on top of ferroelectric BaTiO3 substrates were prepared and a magnetoelectric coupling effect was observed. We employed hereby a magnetoelectric AC susceptibility setup as modification of a commercial superconducting quantum interference device magnetometer. The magnetoelectric coefficient shows two jumps at the BaTiO3 phase transition temperatures. Moreover, the magnetic depth profile of the nanoparticle monolayer was probed by polarized neutron reflectivity. The data recorded at various electric field values show that the electric field is able to alter the magnetism of the nanoparticle monolayer by a strain mediated magnetoelectric coupling effect.